GONADAL DEVELOPMENT OF DOMESTICATED CORAL TROUT (Plectropomus leopardus) REARED IN FLOATING NET CAGE - Sari BM Sembiring; R Andamari; A Muzaki; I K Wardana; J H Hutapea; Ni Wayan Widya A (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2014)
Research on Coral trout breeding has been started since 2002 at the Institute of Mariculture Research and Development and currently some hatcheries are being developed around the institute using natural broodstock. To promote the success on this breeding program, it is necessary to study the reproduction development of domesticated coral trout. The fishes were reared in floating net cage. Observation were conducted on 163 fishes in June 2013 with body weight range from 710 -2020 g (average of 1.393 g) and total length with range of 34-49.5 cm. Fishes were dissected and taken  out their gonad for histology preparedness. Histology analyses found that there were 156 female, 2 hermaprodite, 2 male, and 3 unidentified fishes. All female fishes were on early gonadal development (stage I and II with gonadal maturation index of observed coral trout ranged from 0.1 to 1.83). Further analyses showed that several different stages of gonad were found in the same gonad and concluded that coral trout was multiple spawnning order (asynchrounous). Based on the data above, it was concluded that gonad maturation of Coral trout is able to develop in domestication system in floating net cage. Keywords: Gonad, Coral trout (Plectropomus leopardus), hystology, floating net cage